2018
DOI: 10.4172/2157-7609.1000235
|View full text |Cite
|
Sign up to set email alerts
|

Management of Herbicide Induced Methemoglobinemia

Abstract: Methemoglobinemia is an altered state of haemoglobin that leads to impaired oxygen delivery to the body tissues. Deliberate ingestion of certain herbicides may lead to this condition. Modern herbicides are often synthetic mimics of natural plant hormones that interfere with growth of the target plants. These modern herbicides act by various mechanisms some of them being Acetyl co-enzyme A carboxylase inhibition, aceto lactate synthase inhibition, photosystem II inhibition, 4-hydroxy phenyl pyruvate dioxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…1 Usual pattern of signs & symptoms are cyanosis, low O2 saturation, normal PaO2 (arterial oxygen in ABG) 1 it is found that there is mismatch & disparity between measured Spo2 & PaO2 without any presence of evolving cardiac & respiratory system abnormality which makes to think about suspicion of Methhemoglobinemia. 2 Patient has headache, nausea, vomiting, cynoderma in early stage of toxemia. 1 There is altered mental sensorium progressing to drowsiness, seizures, coma & death in later stages of critical illness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Usual pattern of signs & symptoms are cyanosis, low O2 saturation, normal PaO2 (arterial oxygen in ABG) 1 it is found that there is mismatch & disparity between measured Spo2 & PaO2 without any presence of evolving cardiac & respiratory system abnormality which makes to think about suspicion of Methhemoglobinemia. 2 Patient has headache, nausea, vomiting, cynoderma in early stage of toxemia. 1 There is altered mental sensorium progressing to drowsiness, seizures, coma & death in later stages of critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…1 Insecticides containing biological extract are rich in nitrogenous products, stabilizers & fillers. Methylene blue is treatment of choice in patients other than G6PD deficiency, 2 Ascorbic acid is main stay of treatment in G6PD deficient individuals as methylene blue precipitate hemolysis in these group. 2 Various diagnostic methods include O2 saturation gap (CO-OXIMETRY), 3 multiple wavelength spectrophotometry, 3 filter paper test, 3 potassium cyanide test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations